Exchange Rate Fluctuations and Output in Oil-Producing Countries : The Case of Iran - Kandil, Magda (IMF Working Papers; Working Paper ;, 2007)
Conventional wisdom states that currency depreciation in oil-producing countries are contractionary because demand effects, limited by the prevalence of oil exports priced in dollars, are more than offset by adverse supply effects. Iran, however, has experienced a rapid increase in non-oil exports in the last decade. Against this background, the paper tests whether the conventional wisdom still applies to Iran and concludes that the emergence of the non-oil export sector has made currency depreciation expansionary. The expansionary effect is particularly evident with respect to anticipated persistent depreciation in the long-run. Notwithstanding the varying effects of exchange rate fluctuations on the demand and supply sides of the economy, managing a flexible exchange rate gradually over time towards achieving stability in the real effective exchange rate may strike the necessary balance.